PERAN DUNIA DIGITAL SISTEM INFORMASI MANAJEMEN PEMBELANJAAN ONLINE DAN OFFLINE YANG BEKERJA MELAYANI KONSUMEN - Berliana, Eliya; Nurhalizah, Nadila; Wahyuni, Ningsih; Hertati, Lesi; Terttiaavini; Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
The rapid development of the internet has resulted in profound changes that impact people's lives, enabling them to engage in both offline and online shopping. While traditional offline shopping involves physically visiting stores, online shopping offers the convenience of making purchases remotely. In order to explore the advantages and disadvantages of offline and online shopping, a shopping activity was conducted on Friday, October 14, 2022, on Jalan Pelita, where food was purchased both online and offline. The objective was to identify the benefits and drawbacks of each method. The findings of this study reveal that offline and online shopping have their own distinct advantages and disadvantages, allowing individuals to adapt their choices to their specific needs. Online shopping is advantageous when speed and practicality are desired, especially for repeat purchases. On the other hand, offline shopping is preferred by those who value relaxation, enjoy the ambiance of a physical mall, and appreciate the tactile experience of directly interacting with products and food.